The influence of murattal al-qur'an therapy on the anxiety of patients who will have an MRI examination - Indriyani, Yeni; Rahayu, Tutik; Wuriningsih, Apriliani Yulianti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The anxiety experienced by patients before an MRI examination not only affects the patient's psychological comfort, but can also affect the image results from the MRI. Non-pharmacological nursing intervention to reduce anxiety levels by providing murottal therapy from the Al-Quran Surah Ar-Rahman combined with providing education on MRI examiner procedures. Purpose: To determine the effect of providing Al-Qur'an Surah Ar-Rahman murottal therapy and MRI education on the anxiety level of patients who will undergo an MRI examination. Method: A quasi experiment with a one group pre-post test design. The number of respondents was 65 respondents with a purposive sampling technique, a non-probability sampling technique. The anxiety level instrument uses HARS and SOP for MRI examination education. The data obtained is processed statistically using the Wilcoxon test. Results: The level of anxiety before the Ar-Rahman surah murottal therapy and MRI education was mostly categorized as moderately anxious, amounting to 39 respondents (60.0%) and mildly anxious amounting to 26 respondents (40.0%). After carrying out most of them were categorized as mildly anxious, amounting to 51 respondents (78.5%) followed by those who were not anxious, amounting to 11 respondents (16.9%) and moderately anxious, amounting to 3 respondents (4.6%). Statistical analysis using Wilcoxon obtained a significant p-value of 0.000 < 0.05. Conclusion: There is a significant effect of providing Murottal Surah Ar-Rahman therapy and MRI education on the anxiety of patients who will undergo MRI procedures in the Radiology Department. Keywords: Al-Quran Murottal; Anxiety Levels; MRI Education.